2005
DOI: 10.1021/jf058105e
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Puerarin and Daidzin on Glucose Homeostasis in Mice

Abstract: Puerarin and daidzin are the major isoflavone glucosides found in kudzu dietary supplements. In this study, we demonstrated that puerarin significantly improves glucose tolerance in C57BL/6J-ob/ob mice, an animal model of type 2 diabetes mellitus, blunting the rise in blood glucose levels after i.p. administration of glucose. In contrast, daidzin, the O-glucoside, had a significant but opposite effect, impairing glucose tolerance as compared to saline-treated controls. When they were administered i.p. with (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 35 publications
7
76
0
Order By: Relevance
“…16) Health effects of daidzin have been proved on memory impairment, hepatic failure, and glucose homeostasis. [17][18][19] It was also reported that glycitin has preventive effect on bone loss and osteonecrosis. 20,21) However, to our knowledge, there are few studies that have been done on the effects of glycoside-form isoflavone supplementation on lipid metabolism associated with diabetes mellitus.…”
mentioning
confidence: 97%
“…16) Health effects of daidzin have been proved on memory impairment, hepatic failure, and glucose homeostasis. [17][18][19] It was also reported that glycitin has preventive effect on bone loss and osteonecrosis. 20,21) However, to our knowledge, there are few studies that have been done on the effects of glycoside-form isoflavone supplementation on lipid metabolism associated with diabetes mellitus.…”
mentioning
confidence: 97%
“…However, 100 M or larger concentrations of puerarin required for in vitro assay were shown to be higher than the approximately 20 M concentrations of puerarin in blood when puerarin was intraperitoneally administered to mice (45). The macrophage activation assay using RAW264.7 might not reflect the in vivo response of macrophages.…”
Section: Discussionmentioning
confidence: 91%
“…The active constituents administered orally are absorbed by the mucosal epithelial cells where they are transported to the liver by hepatic portal vein. These constituents are metabolized in the liver after which reduced amounts of un-metabolized constituents are released into the systemic circulation [20]. Table 3: Quantitative screening of the phytochemicals in the medicinal plants extract.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemicals present in aqueous leaves extract of Vernonia lasiopus (saponins, flavonoids, alkaloids, sterols, and tannins) were determined using standard procedures [19,20].…”
Section: Determination Of Phytochemicalsmentioning
confidence: 99%